Association of e-cigarette and cigarette use with self-reported chronic obstructive pulmonary disease (COPD): a multivariable analysis of a large United States data set - Alicia J. Burns; Alexander W. Steinberg; James D. Sargent; Jenny E. Ozga; Zhiqun Tang; Cassandra A. Stanton; Laura M. Paulin (Respiratory Research)
Abstract Background Prior research has linked e-cigarette use with chronic obstructive pulmonary disease (COPD). We examined the relationship between e-cigarette use and COPD prevalence in older adults with varying cigarette use status. Methods Data from the 2020 National Health Interview Survey were used to estimate the association between each of 9 exposure categories based on cigarette use (never, former, current) and e-cigarette use (never, former, current), with respondent-reported physician-diagnosed COPD prevalence in individuals 40 years and older (N = 22,997). Weighted multivariable analysis accounted for cigarette pack years, age of cigarette smoking onset, race, income-to-poverty ratio, rurality, gender, age, and medical comorbidities. Sensitivity of results was tested in 3 separate models with addition of years since quit cigarettes, smoking intensity and duration. Results 39.7% of individuals reported ever smoking cigarettes and 10.2% reported ever using e-cigarettes. Among individuals with ever e-cigarette use, 88.5% also reported current or former cigarette smoking. The weighted prevalence of COPD was 7.2%; Among those who reported former cigarette smoking, the highest risk of COPD prevalence compared to never cigarette/never e-cigarette use was in those currently using e-cigarettes (adjusted risk ratio (ARR) 2.82, 95% confidence interval (CI) [1.5, 5.3]). The ARR for former cigarette/current e-cigarette use was significantly larger than the ARR for former cigarette/never e-cigarette use (p < 0.002) in 3 out of 4 models; however, one model had the ARR attenuated to 1.35 (0.67, 2.76) when years since quitting smoking was added to the model. Other cigarette/e-cigarette combinations were also sensitive to how cigarette smoking history was modeled. For example, ARR for former cigarette/former e-cigarette (1.68 [1.00, 2.80] and current cigarette/former e-cigarette (2.50 [1.56,4.02]) were reduced to 1.05 (0.62, 1.77) and 1.04 (0.62, 1.75) respectively, when cigarette smoking duration was substituted for pack-years. Conclusions Current e-cigarette use among former cigarette smokers was associated with significantly higher COPD prevalence compared to never e-cigarette use. However, COPD risk for most cigarette/e-cigarette combinations could be greatly attenuated by how cigarette smoking history was modeled, raising questions about the robustness of these associations in prior research and the possibility of reverse causality in prior cross-sectional research.